2015
DOI: 10.1590/1516-3180.20151331t2
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal versus monofocal intraocular lenses after cataract extraction

Abstract: Sixteen completed trials (1608 participants) and two ongoing trials were identified. All included trials compared multifocal and monofocal lenses but there was considerable variety in the make and model of lenses implanted. Overall we considered the trials at risk of performance and detection bias because it was difficult to mask patients and outcome assessors. It was also difficult to assess the role of reporting bias. There was moderate quality evidence that similar distance acuity is achieved with both type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 2 publications
3
29
0
5
Order By: Relevance
“…Both groups performed relatively similar in obstacle clearance with no substantial differences. Our findings are consistent with the findings of Calladine et al, in which monofocal and multifocal IOLs were similar at all distances, except where multifocal IOLs improved near sight [28]. If both IOLs perform similarly at moderate visual distances, then it can be theorized that clearances would be similar.…”
Section: Monofocal Versus Multifocal Lensessupporting
confidence: 92%
“…Both groups performed relatively similar in obstacle clearance with no substantial differences. Our findings are consistent with the findings of Calladine et al, in which monofocal and multifocal IOLs were similar at all distances, except where multifocal IOLs improved near sight [28]. If both IOLs perform similarly at moderate visual distances, then it can be theorized that clearances would be similar.…”
Section: Monofocal Versus Multifocal Lensessupporting
confidence: 92%
“…Lower contrast sensitivity and higher incidence of photic phenomena, such as halos and glare, have been reported with multifocal IOLs compared with monofocal IOLs, 3,10 despite good vision over a range of distances and spectacle independence achieved with multifocal IOLs. 14,15 At the 1-year follow-up visit of a randomized prospective clinical trial, halo and glare were reported to be more common with refractive multifocal IOLs compared with diffractive IOLs, and contrast sensitivity in patients with diffractive multifocal IOLs was similar or superior to that in patients who received monofocal IOLs or refractive multifocal IOLs.…”
Section: Discussionmentioning
confidence: 95%
“…Despite improvements in surgical techniques and outcomes, patients often require multifocal spectacles for near visual acuity and residual astigmatic error after surgery. 3 Postoperative dependence on vision correction is one of several factors that contribute to diminished vision-related quality of life after cataract surgery. The goal of this study was to evaluate and compare visual outcomes, spectacle independence, and quality of life among nonastigmatic and astigmatic patients who received AcrySof IQ ReSTOR toric or nontoric multifocal IOLs compared with those who received commercially available monofocal IOLs following bilateral cataract removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] In cataract surgery, multifocal IOL implantation substantially solved the problem of near vision without eyeglasses and without impairing distance vision, which could not be achieved with classical monofocal IOLs. [4][5][6] However, it was reported that depth of focus reduces and problems such as blurred vision, photophobia, halo and glare are more prevalent in the patients that underwent multifocal IOL implantation and have uncorrected corneal astigmatism of 0.75 diopter and over. [7][8][9] In addition to correction of refractive defect and enabling near vision without the need for eyeglasses, also correction of astigmatism has been possible with multifocal toric IOL that has been manufactured recently.…”
Section: Introductionmentioning
confidence: 99%